On calcium-to-alkalinity anomalies in the North Pacific, Red Sea, Indian Ocean and Southern Ocean. (15th June 2021) - Steiner, Zvi; Sarkar, Amit; Liu, Xuewu; Berelson, William M.; Adkins, Jess F.; Achterberg, Eric P.; Sabu, P.; Prakash, Satya; Vinaychandran, P.N.; Byrne, Robert H.; Turchyn, Alexandra V.
Abstract: An important factor for predicting the effect of increased CO2 on future acidification of the ocean is a proper understanding of the interactions controlling production and dissolution of calcium carbonate minerals (CaCO3 ). The production and dissolution of CaCO3 in the ocean can be assessed over large spatial scales by measuring seawater calcium concentrations and total alkalinity (AT ), yet past studies suggest that there could be large discrepancies between calcium and AT -based balances of the CaCO3 cycle in the North Pacific and Indian Oceans. Here, we analyse water column samples collected along transects in the North Pacific, Southern Ocean, tropical Indian Ocean and Red Sea for their concentrations of calcium, nutrients, and AT . We find that there is an excess calcium over AT anomaly in the top 1000 m of the tropical Indian Ocean water-column. The source of this anomaly is the dissolution of subsurface gypsum deposits in the Red Sea. We find no evidence for calcium-over-AT anomalies in the North Pacific, in contrast to previous studies. Our results show that, in most cases, calcium and AT data agree well and can be used to reconstruct the marine CaCO3 cycle.